MUHAMMAD SYAHRUR DAN KONSEP MILKUL YAMIN : KRITIK PENAFSIRAN PERSPEKTIF USHUL FIQH - Mukhammad Nur Hadi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2019)
The Scholars stated that occurring verses of milkul yamin (slave ownership) had been stoped because of its locus which was disappeared. Meanwhile, the trademark of al-Qur’an as the book of revelation which is always relevant unlimitedly to dynamic of era has been paradox. On the other hand, through Syahrur verses of milkul yamin uniquely can be interpreted with the new locus. Syahrur assumed that nowadays the context of milkul yamin can be compared with ‘aqdul ihshan (commitment of sexual intercourse) as the way to legitimate sexual intercourse outside marriage that is happening in the Western tradition. This concept was based on sexual intercourse between man and his slave which was taken from three chapters; al-Ahzab: 50, al-Mu’minun: 5-6, and an-Nur: 31 as a consequence of the view of Syahrur’s limit theory to the comprehnsive norm of al-Qur’an. However, the problem is that is reinterpretation of Syahrur relevant accordance with the principal orinentation of al-Qur’an (maqashid al-Qur’an). Ideally, the recontextualization should considered general benefits (mashlahat) for human because not all traditions can be accommodated by Islam. It shows that living Qur’an to verses of milkul yamin on Syharur’s perspective ignored the dialectic between mashlahat (benefit) and ‘urf (tradition).  In this position, reexamining Syharur’s thought of his reinterpretation to milkul yamin by considering the ideal of human-social reality does not find base paradigm.